The Ability in Understanding Simple Future Tense at Tenth Grade Students of Senior High School 3 Jambi City - Alberd Alberto Ardiansyah; Yanti Ismiyati; Nurul Fitri (Universitas Batanghari Jambi, 2022)
The ability of students to understand the learning material is important. When students are able to understand the material given by the teacher, then they can apply the knowledge theoretically or in action. A simple way to check students' understanding or ability is through written assessments and student skills. This research was appointed to find out how far the students' ability in understanding grammar, in this case is the Simple Future Tense. This study uses quantitative as a research design and descriptive as research methodology. This study took a population of tenth graders at SMA 3 Jambi City in the 2021/2022 academic year and the sample was students in class X MIPA 6 in the 2021/2022 academic year. This study uses a test given to the respondents as a research instrument, then the results of the test are assessed and analyzed. The average value of the test obtained is 56.27. On the other hand, the value of the standard deviation obtained is 33.017. As a result, 11 respondents from the sample received the predicate